Results of Liver Transplantation for Hepatocellular Carcinoma in a Multicenter Latin American Cohort Study (2018)
ABSTRACT: Background and aims. Background and aims. Heter Background and aims. ogeneous data has been reported regarding liver transplantation (LT) for hepatocellular carcinoma (HCC) in Latin America. We aimed to describe treatment during waiting list, survival and recurrence of HCC after LT in a multicenter study from Latin America. Material and methods. Material and methods. Patients with Material and methods. HCC diagnosed prior to transplant (cHCC) and incidentally found in the explanted liver (iHCC) were included. Imaging-explanted features were compared in cHCC (non-discordant if pre and post-LT were within Milan, discordant if pre-LT was within and post-LT exceeding Milan). Results. Overall, Results.Results. 435 patients with cHCC and 92 with iHCC were included. At listing, 81% and 91% of cHCC patients were within Milan and San Francisco criteria (UCSF), respectively. Five-year survival and recurrence rates for cHCC within Milan, exceeding Milan/within UCSF and beyond UCSF were 71% and 16%; 66% and 26%; 46% and 55%, respectively. Locoregional treatment prior to LT was performed in 39% of cHCC within Milan, in 53% beyond Milan/within UCSF and in 83% exceeding UCSF (p < 0.0001). This treatment difference was not observed according to AFP values (d100, 44%; 101-1,000, 39%, and > 1,000 ng/mL 64%; p = 0.12). Discordant imaging-explanted data was observed in 29% of cHCC, showing lower survival HR 2.02 (CI 1.29; 3.15) and higher recurrence rates HR 2.34 when compared to AFP <100 ng/mL. Serum AFP > 1,000 ng/mL at listing was independently associated with a higher 5-year recurrence rate and a HR of 3.24 when compared to AFP <100 ng/mL. Conclusion. Although overall r Conclusion.Conclusion. esults are comparable to other regions worldwide, preLT treatment not only considering imaging data but also AFP values should be contemplated during the next years.